Atmospheric Drag Perturbation On Weather Satellite At Two Different Geomagnetic Fields Conditions - Najlaa Ozaar Hasan; Ahmed Kader Izzet; Hindreen A. Ibrahim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This study analyzes the effect of atmospheric drag perturbation at two different magnetic index (active and severe storm) conditions, on the motion of NOAA 15 weather satellite, the Celestial Mechanics software results were plotted with the assistance of the MATLAB program. From the results it is noticed that for short period of time the effect of atmospheric suppression disturbance at different geomagnetic activity had the same effect on the orbital elements and orbital motion components , for a long period there is a slight variation in the effect of the perturbation at two different geomagnetic activities, which can be seen in the orbit's inclination as well as its size and shape. The results demonstrated that motion components were significantly impacted by geomagnetic activity over relatively extended time scales.